2012
DOI: 10.5812/asjsm.34607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morning Caffeine’ Ingestion on Mood States, Simple Reaction Time, and Short-Term Maximal Performance on Elite Judoists

Abstract: PurposeThe purpose of the present study was to evaluate the ergogenic effect of caffeine ingestion on mood state, simple reaction time, and muscle power during the Wingate test recorded in the morning on elite Judoists.MethodsTwelve elite judoists (age: 21.08 ± 1.16 years, body mass: 83.75 ± 20.2 kg, height: 1.76 ±6.57 m) participated in this study. Mood states, simple reaction time, and muscle power during the Wingate test were measured during two test sessions at 07:00 h and after placebo or caffeine ingesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…Indeed, the enhanced reaction time aff orded by energy shots over the placebo in the current study mimics results of others ( Jacobson & Edgley, 1987 ;Souissi, et al ., 2012 ). However, such small diff erences (msec.)…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the enhanced reaction time aff orded by energy shots over the placebo in the current study mimics results of others ( Jacobson & Edgley, 1987 ;Souissi, et al ., 2012 ). However, such small diff erences (msec.)…”
Section: Discussionsupporting
confidence: 90%
“…Another study reported improved reaction times while at the same time increasing perceptions of alertness and focus ( Hoff man, Kang, Ratamess, Hoff man, Tranchina, & Faigenbaum, 2009 ). More recently researchers have found caff eine reduces simple reaction time ( Howard & Marczinski, 2010 ;Souissi, Abedelmalek, Chtourou, Atheymen, Hakim, & Sahnoun, 2012 ),…”
mentioning
confidence: 99%
“…However, it is possible that slow-twitch fibers are more sensitive to such action than fast-twitch fibers 34,35 , which could help to explain the limited ergogenic effect upon maximal strength and muscle power. In their evaluation of the contractile properties of skeletal muscle, Souissi et al 24 , Souissi et al 25 , Silva et al 23 and Glaister et al 26 suggest that the positive benefit of caffeine use in cyclists may be more effective in longer time evaluations of muscle power compared to shorter tests. Thus further research is needed to elucidate the ergogenic effects of caffeine during muscle strength exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these studies [23][24][25] used the Wingate test; the other study 26 used seven sprints for a maximum of 10 seconds. The average dosage of caffeine was 6.5 mg/kg of body weight.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…In contrast, a slight improvement in reaction time has been seen following the ingestion of caffeine. 29,34,86,87 This finding may allow athletes who supplement with caffeine to mask the deficits in reaction time following a concussion.…”
Section: Reaction Timementioning
confidence: 89%